Informal environmental education on example of regional press in lubelskie province - Stoczkowska, Renata; Obrębska, Maria; Kowalski, Ryszard; Maluchnik-Pucek, Magdalena (Studia Ecologiae et Bioethicae, 2006)
The press fulfills an important role if it comes to culture, it also influences the public opinion, therefore, it can be an important tool in forming the view of society according to the problems of degradation and protection of the natural environment, the aim of this article is to estimate engagement of the regional press on the example of lubelskie province, the hypothesis is that the regional daily press in lubelskie province leads informal environmental education, however, they do not use their potential and means in order to form pro-ecological attitudes and opinions among its readers, the results of the research have shown that the number of articles about nature has systematically increased comparing to other thematic ranges, which is a very positive fact. However, the texts which are sensational and do not touch the problem still prevail in the press, there are not enough articles that present the natural environment as a value that should be protected because of economic, spiritual, healthy, and esthetic reasons. Taking into account that the problems connected with degradation and protection of nature ought to be treated as a priority, the local press should involve in the environmental education much stronger, they can get through to the readers by interesting and convincing articles, and contribute to the improvement of the natural environment.